Studi Komparatif antara Ekonomi Konvensional dan Ekonomi Syariah: Konsep, Prinsip, dan Implementasi - Abu lubaba; Arifahtul Hikmah; Raisya Putri Natasya; Afif Al Khaedar; Falah Alkautsar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze and compare conventional economics and Islamic economics in terms of their concepts, principles, and implementation in economic activities. Conventional economics is an economic system oriented toward achieving profit and efficiency through market mechanisms, with individual rationality and economic freedom as its primary foundations. In contrast, Islamic economics is an economic system guided by Islamic values derived from the Qur'an and Hadith, aiming to achieve welfare (falah), justice, and a balance between individual and social interests. The research employs a library research method with a descriptive-comparative approach. Data were collected through a review of various relevant literature sources, including scientific journals, books, and official documents related to conventional and Islamic economics. The findings indicate that there are fundamental differences between the two economic systems. Conventional economics emphasizes material aspects and profit maximization through interest-based mechanisms, whereas Islamic economics promotes principles of justice, the prohibition of riba (usury), profit-and-loss sharing, and social responsibility. In practice, Islamic economics is implemented through Islamic financial institutions, Islamic banking, zakat, infaq, sadaqah, and waqf, which contribute to the equitable distribution of social welfare. Although both systems share the objective of improving economic welfare, Islamic economics offers a more comprehensive approach by integrating both material and spiritual dimensions. Therefore, Islamic economics can serve as an alternative economic system capable of fostering stability, justice, and sustainability in economic development.